2011
DOI: 10.1080/15257770.2011.616564
|View full text |Cite
|
Sign up to set email alerts
|

Apical Voltage-Driven Urate Efflux Transporter NPT4 in Renal Proximal Tubule

Abstract: Uric acid (urate) is the end product of purine metabolism in humans. Human kidneys reabsorb a large proportion of filtered urate. This extensive renal reabsorption, together with the fact that humans do not possess uricase that catalyzes the biotransformation of urate into allantoin, results in a higher plasma urate concentration in humans compared to other mammals. A major determinant of plasma urate concentration is renal excretion as a function of the balance between reabsorption and secretion. We previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 29 publications
0
28
0
2
Order By: Relevance
“…As was the case with reduced renal function, we found that concomitant use of diuretics did not significantly alter the concentration –response to oxypurinol or dose –response relationship to allopurinol. Diuretics decrease not only the renal transport of urate ( via inhibition of proximal tubule transporters ) but also the clearance of oxypurinol . Similar to the effect of renal impairment on urate and oxypurinol clearance, the reductions in oxypurinol clearance results in higher plasma concentrations, which negates the decrease in urate clearance.…”
Section: Discussionmentioning
confidence: 99%
“…As was the case with reduced renal function, we found that concomitant use of diuretics did not significantly alter the concentration –response to oxypurinol or dose –response relationship to allopurinol. Diuretics decrease not only the renal transport of urate ( via inhibition of proximal tubule transporters ) but also the clearance of oxypurinol . Similar to the effect of renal impairment on urate and oxypurinol clearance, the reductions in oxypurinol clearance results in higher plasma concentrations, which negates the decrease in urate clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, diuretics are one of the most important causes of secondary HU. Loop diuretics and thiazide diuretics interact with renal organic anion transporters (OAT), entering the proximal tubular cell from the blood side via OAT1 and OAT3 transporters may be considered as competitive substrates of uric acid [30]. Moreover, diuretics reduce uric acid excretion, presumably by causing mild volume depletion with enhancement of proximal tubular reabsorption [31].…”
Section: Discussionmentioning
confidence: 99%
“…КЛИНИЧЕСКИЕ СЕМИНАРЫ § канальца, снижает секрецию ОАи диуретиков. Уремия и метаболический ацидоз -типические состояния, ведущие к резистентности к диуретикам [15,28]. Лечение ХБП состоит не только в контроле отеков, но и АГ, метаболического ацидоза и гиперкалиемии.…”
Section: толерантность к петлевым мочегонным средствамunclassified